The algorithm for predicting reservoir properties of rocks basing on the information properties of the mutual phase spectrum of reflected seismic waves; Молодежь и современные информационные технологии - Sidorenko S. N. (Математическое моделирование и компьютерный анализ данных, 2013)
Заглавие с титульного экрана